Endogenous intoxication syndrome in rats consuming drinking water with different phosphate contents - LototskaOlenа; Bandrivska, Yulia (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2023)
Abstract. Endogenous intoxication plays a significant role in the pathogenesis of many diseases. The erythrocyte intoxication index and molecular weight medium are informative indicators for its research. The goal is to establish the degree of expression of endogenous intoxication syndrome in white rats against the background of drinking water with different phosphate content for 30 days. Materials and methods. The study was conducted on 36 white purebred male rats weighing 180-200 g, divided into six groups, which for 30 days consumed: the control group – settled water from the city waterworks, the animals of five experimental groups - water with the addition of sodium monophosphate in doses of 100.0; 10.0; 1.0; 0.1; 0.01; mg/dm3 in terms of elemental phosphorus. The level of endogenous intoxication was estimated by the content of molecular weight medium in blood serum at wavelengths λ = 254 and 280 nm and the level of erythrocyte intoxication index, which was determined using the method of A. A. Togaibaev, et al., which is based on the ability of the erythrocyte membrane to absorb methylene blue. Results. It was established that the content of molecular weight medium 254 in the blood serum of experimental animals significantly increased in the 1st group by 65 % (p < 0.05), the content of molecular weight medium 280 in the 1st group by 154 % (p < 0.05), in the 2nd – by 138 % (p < 0.05) and the 3rd – by 64 % (p < 0.05). Consumption of drinking water with added phosphates leads to a significant increase of erythrocyte intoxication index in the 1st group – by 186 % (p < 0.05), in the 2nd – by 142 % (p < 0.05) compared to the control. Conclusions. Consumption of drinking water with different phosphate content for 30 days causes an increase in the level of endogenous intoxication in the body of experimental rats, as indicated by an increase in the permeability of erythrocyte membranes and an increase in the erythrocyte intoxication index and molecular weight medium content, most pronounced at a concentration of 100.0 mg/dm3.